2011
DOI: 10.15282/jmes.1.2011.8.0008
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of External Mixture Formation Strategy in Hydrogen Fueled Engine

Abstract: Hydrogen induction strategy in an internal combustion engine plays a vital role in increasing the power density and prohibiting combustion anomalies. This paper inspects the performance characteristics of cylinder hydrogen-fueled engine with port injection feeding strategy. To that end, a one-dimensional gas dynamic model has been built to represent the flow and heat transfer in the components of the engine. The governing equations are introduced followed by the performance parameters and model description. Ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…The greenhouse effect is a worldwide issue as more and more greenhouse gases are released into the atmosphere, leading to global climate change [1][2][3][4][5][6]. The effects include an increase in temperature, unstable weather and rising ocean levels, resulting from ice melting at the North and South Poles [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The greenhouse effect is a worldwide issue as more and more greenhouse gases are released into the atmosphere, leading to global climate change [1][2][3][4][5][6]. The effects include an increase in temperature, unstable weather and rising ocean levels, resulting from ice melting at the North and South Poles [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Combustion is predicted to be the most important way of generating future energy [1,[3][4][5][6]. Fuel depletion and emission is the main issue to cater this energy need [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Biodiesel contains 10-12% oxygen in weight basis and this lowers the energy content. The lower energy content causes reductions in engine torque and power [2,[4][5][6][7]. It has been reported that biodiesel containing oxygen reduces exhaust emissions such as HC and CO mainly because of complete combustion.…”
Section: Introductionmentioning
confidence: 99%